Characterization and use of an unprecedentedly bright and structurally non-perturbing fluorescent DNA base analogue. - Sandin, P; Börjesson, K; Li, H; Mårtensson, J; Brown, T; Wilhelmsson, L; Albinsson, B (2008)
This article presents the first evidence that the DNA base analogue 1,3-diaza-2-oxophenoxazine, tC(O), is highly fluorescent, both as free nucleoside and incorporated in an arbitrary DNA structure. tC(O) is thoroughly characterized with respect to its photophysical properties and structural performance in single- and double-stranded oligonucleotides. The lowest energy absorption band at 360 nm (epsilon = 9000 M(-1) cm(-1)) is dominated by a single in-plane polarized electronic transition and the fluorescence, centred at 465 nm, has a quantum yield of 0.3. When incorporated into double-stranded DNA, tC(O) shows only minor variations in fluorescence intensity and lifetime with neighbouring bases, and the average quantum yield is 0.22. These features make tC(O), on average, the brightest DNA-incorporated base analogue so far reported. Furthermore, it base pairs exclusively with guanine and causes minimal perturbations to the native structure of DNA. These properties make tC(O) a promising base analogue that is perfectly suited for e.g. photophysical studies of DNA interacting with macromolecules (proteins) or for determining size and shape of DNA tertiary structures using techniques such as fluorescence anisotropy and fluorescence resonance energy transfer (FRET).